Pengaruh Promosi, Harga Dan Lokasi Terhadap Minat Beli Konsumen Rocket Chicken, Tlogomas Kota Malang - Ubaydillah, Awaluddin; Widarko, Agus; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aimed to examine and analyze the impact of promotion, price, and location on consumer purchasing interest at Rocket Chicken Tlogomas, Malang City. An explanatory research method with a quantitative approach was employed, utilizing a Likert scale for measurement. The sample was chosen through a non-probability sampling method, specifically the snowball sampling technique, involving a total of 100 respondents. Primary data was collected through a questionnaire distributed via Google Forms. The data analysis in this study involved validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and determination tests, conducted using SPSS 26 software. The findings reveal that promotion, price, and location collectively influence consumer purchasing interest. Promotion affects consumer purchasing interest. Price affects consumer purchasing interest. Location affects consumer purchasing interest. Keywords: Promotion, Price, Location, Consumer Buying Interest